Rural tourism in the conditions of the paradigm of sustainable development - Лариса Безкоровайна; Larysa Bezkorovaina; Венгерська Наталя; Natalia Venherska; Валентина Воронкова; Valentina Voronkova; Regina Andriukaitiene; Щука Галина; Scsuka Halina; Shchuka Halyna (Kolping Higer Education Institution, 2024)
Abstract. Among the goals of sustainable development, the tourism industry is one of the largest global industries. The sustainable development of tourism is taking into account the current and future economic, social, and environmental consequences of tourism activities in accordance with the requirements of travelers, the specifics of the tourism industry, and environmental conditions. Rural tourism as a type of tourism satisfies society's needs for rest, recreation, knowledge of the environment and its harmless use, development of rural areas. Therefore, the question of studying rural tourism is relevant.
Keywords: sustainable development; rural tourism